Ginástica rítmica e especialização precoce: caminhos das pesquisas e publicações no Brasil - Cardoso, Thays Caroline dos Santos [UNESP] (Universidade Estadual Paulista (Unesp), 2013)
This final course project originates itself from the discussions of the Group of Studies and Pedagogical Research in Gymnastics (GEPPEGIN) of Unesp/RC and starts with the Pedagogy of Sport, with the purpose of knowing, analysing and discussing its existence and paths, in a series of discussions about the early specialization. The early specialization is a theme that relates frequently to the modalities of gymnastics, the focus point being that most gymnasts are specialized younger than most athletes from other sports (SCHIAVON, 2009), and not always in a proper way. It is from this issue that the intention of this study begins: knowing, analysing and discussing the existence and the ways of discussions about early specialization in researches and publications related to Rhythmic Gymnastics in the last decade (2002-2012) in Brazil. For the development of this qualitative research of scientific initiation a bibliographic research will be conducted about Rhythmic Gymnastics, with the focus on arising researches from post graduation programs stricto-sensu, recognized by Capes and, scientific papers, published during indexed periods in Brazil and classified in Qualis of Physic Education

O presente trabalho de conclusão de curso origina-se a partir de discussões do Grupo de Estudos e Pesquisas Pedagógicas em Ginástica (GEPPEGIN) da Unesp/RC e tem como ponto de partida a Pedagogia do Esporte, com o propósito de conhecer, analisar e discutir a existência e os caminhos, das discussões sobre especialização precoce. A especialização precoce é um tema bastante relacionado às modalidades ginásticas, tendo em vista que ginastas são especializados em faixa etária anterior à da maioria de atletas de outras modalidades esportivas (SCHIAVON, 2009), e nem sempre de forma adequada. A partir desta problemática, surge o objetivo deste estudo: conhecer, analisar e discutir a existência e os caminhos das discussões sobre especialização precoce em pesquisas e publicações relacionadas à Ginástica Rítmica na última década (2000-2012) no Brasil. Para o desenvolvimento dessa pesquisa qualitativa de iniciação científica será realizada uma pesquisa bibliográfica sobre Ginástica Rítmica, com foco em pesquisas oriundas de programas de pós-graduação stricto-sensu, reconhecidos pela Capes e, artigos científicos, publicados em periódicos indexados no Brasil e classificados no Qualis da Educação Física
Keywords: Ginástica; Ginastica ritmica; Especialista; Esportes infantis; Ginastas; Publicações cientificas